The role of shrimp miR-965 in virus infection. (July 2016) - Shu, Le; Li, Changrun; Zhang, Xiaobo
Abstract: RNAi, mediated by microRNAs (miRNAs), has attracted increasing attention for its important role in cross-talk between host and virus. However, the role of host miRNA in the virus infection in vivo has not been intensively investigated. In this study, the effects of a shrimp miRNA (miR-965) on the white spot syndrome virus (WSSV) infection were characterized. The results indicated that the expression of miR-965 was significantly upregulated in shrimp in response to the WSSV challenge, suggesting its involvement in the virus infection. The miR-965 silencing led to significant increases of WSSV copies and virus-infected shrimp mortality, while the miR-965 overexpression resulted in the decreased WSSV copies and virus-infected shrimp mortality, indicating that miR-965 played a negative role in the WSSV infection. The further data revealed that miR-965 inhibited the virus infection by targeting the viral wsv240 gene, an important gene required for the WSSV infection in shrimp. The results demonstrated that miR-965 could promote the shrimp phagocytosis against virus infection by targeting the shrimp ATG5 (autophagy related 5) gene. Therefore, our findings presented novel evidence to better understand the anfractuous host-virus interactions in vivo . Highlights: Our findings presented that shrimp miR-965 played a negative role in the virus infection. Shrimp miR-965 inhibited the white spot syndrome virus (WSSV) infection by directly targeting the viral wsv240 gene. The viral wsv240 gene, an early WSSV gene, was required for the WSSV infection in shrimp. Shrimp miR-965 promoted the antiviral phagocytosis of shrimp by targeting the shrimp ATG5 (autophagy related 5) gene.